Relationship between Reproductive Allocation and Relative Abundance among 32 Species of a Tibetan Alpine Meadow: Effects of Fertilization and Grazing - Niu, Kechang; Schmid, Bernhard; Choler, Philippe; Du, Guozhen (PLOS ONE, 2012)
Background Understanding the relationship between species traits and species abundance is an important goal in ecology and biodiversity science. Although theoretical studies predict that traits related to performance (e.g. reproductive allocation) are most directly linked to species abundance within a community, empirical investigations have rarely been done. It also remains unclear how environmental factors such as grazing or fertilizer application affect the predicted relationship. Methodology We conducted a 3-year field experiment in a Tibetan alpine meadow to assess the relationship between plant reproductive allocation (RA) and species relative abundance (SRA) on control, grazed and fertilized plots. Overall, the studied plant community contained 32 common species. Principal Findings At the treatment level, (i) RA was negatively correlated with SRA on control plots and during the first year on fertilized plots. (ii) No negative RA–SRA correlations were observed on grazed plots and during the second and third year on fertilized plots. (iii) Seed size was positively correlated with SRA on control plots. At the plot level, the correlation between SRA and RA were not affected by treatment, year or species composition. Conclusions/Significance Our study shows that the performance-related trait RA can negatively affect SRA within communities, which is possibly due to the tradeoffs between clonal growth (for space occupancy) and sexual reproduction. We propose that if different species occupy different positions along these tradeoffs it will contribute to biodiversity maintenance in local communities or even at lager scale.